Real-life X-files : investigating the paranormal - Nickell, Joe (Lexington, Ky. : University Press of Kentucky, 2001)
As a former private investigator and forensic writer, Joe Nickell has spent much of his career identifying forged documents, working undercover to infiltrate theft rings, and investigating questioned deaths. Now he turns his considerable investigative skill toward the paranormal, researching the most well-known and mysterious phenomena all over the world-spontaneous human combustion, UFO visitations, auras, electronic poltergeists, and many, many more-with an eye toward solving these mysteries rather than promoting or dismissing them. Real-Life X-Files: Investigating the Paranormal examines the.
The case of the petrified girl -- The Devil's footprints -- Magicians among the spirits -- The specter of spontaneous human combustion -- Believe it or--? -- Legend of the "miraculous stairway" -- Flying saucer "dogfight" -- A study in clairvoyance -- The Kennedy curse -- Riddle of the circles -- Cult of the "UFO missionaries" -- The electronic poltergeist -- The Silver Lake serpent -- Miraculous rose petals -- Paranormal Lincoln -- The Roswell legend -- Investigating police psychics -- Ghostly photos -- The Lake Utopia monster -- Memory of a past life -- Photographing the aura -- Mystery of the Holy Shroud -- The giant frog -- The alien likeness -- In search of "snake oil" -- The haunted cathedral -- Miracle photographs -- The gypsies' "great trick" -- Magnetic Hill -- Phantom ship -- The cryptic stone -- Communicating with the dead? -- Jesus among the clouds -- Alien implants -- Sleuthing a psychic sleuth -- Adventure of the weeping icon -- The secrets of Oak Island -- Enigma of the crystal tears -- Death of the fire-breathing woman -- Comatose "miracle worker" -- Extraterrestrial autopsy -- Spirit paintings -- Watching the spirits paint -- Sitgmata -- Haunted inns -- The Flatwoods UFO Monster -- Milk-drinking idols.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Parapsychology -- Case studies; Curiosities and wonders; Impostors and imposture; Parapsychologie -- Études de cas; Curiosités et merveilles; BODY, MIND & SPIRIT -- Parapsychology -- General; SOCIAL SCIENCE -- Conspiracy Theories; Curiosities and wonders; Impostors and imposture; Parapsychology; Case studies